Five years on: the monster flare of 2017. Issue 5 (1st October 2022) - French, Ryan
Abstract : Ryan French looks back at a momentous event, both in the history of solar physics, and his own career. Abstract: Ryan French looks back at a momentous event, both in the history of solar physics, and his own career.